Comparison of contrast-enhanced ultrasound and contrast-enhanced computed tomography for the diagnosis of cervical lymph node metastasis in squamous cell carcinoma of the oral cavity. Issue 3 (March 2021) - Ding, Z.; Deng, C.; Wang, Z.; Liu, L.; Ma, X.; Huang, J.; Wang, X.; Xuan, M.; Xie, H.
Abstract: Early detection of cervical lymph node metastasis (CLNM) from squamous cell carcinoma (SCC) of the oral cavity remains challenging. This prospective study was performed to evaluate the ability of contrast-enhanced ultrasound (CEUS) to detect CLNM from oral cavity SCC. Additionally, its diagnostic value was compared with that of contrast-enhanced computed tomography (CECT). Forty-eight consecutive patients with SCC of the oral cavity were enrolled. All subjects were examined preoperatively with both CEUS and CECT. Subsequently, neck dissections were performed for these patients, and cervical lymph nodes separated from the surgical specimens were assessed histologically. The diagnostic performance of these two examinations was compared based on the results of histopathology. The sensitivity, specificity, accuracy, positive predictive value, negative predictive value, and Youden index for CEUS and CECT were 69.39% vs. 44.90%, 94.71% vs. 97.12%, 89.88%% vs. 87.16%, 75.56% vs. 78.57%, 92.92% vs. 88.21%, and 64.10% vs. 42.02%, respectively. A significant difference was observed in terms of sensitivity ( P  = 0.024) and Youden index (rate difference 22.08%, 95% confidence interval 2.72–41.44%). Therefore, CEUS appears to be a promising diagnostic tool that is superior to CECT for detecting CLNM from SCC of the oral cavity, with a higher sensitivity.